2018
DOI: 10.1002/pc.25056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Barrier Properties Enhancement in Film Extruded Bio‐Polyamides With Modified Nanoclay

Abstract: The plastics industry is increasingly oriented towards the use of bio‐based polymers replacing the fossil‐based ones. Bio‐based polyamides (PAs) in the film packaging application are not still used and need enhancement to overcome some drawbacks. In this scenario, fully (PA10.10) and partially (PA6.10) bio‐based PAs were extruded in a laboratory sheet‐casting machine. The materials used to obtain films were previously melt blended with modified clay in a twin‐screw extruder. The resulting films were morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The disappearance of this peak by transmission XRD and appearance by reflection XRD analysis confirms the assumption about the preferential orientation of clay crystallites in the PAnanoclay composite. Abdelwaha et al [16] observed a similar preferred orientation effect for polyamide-Nanomer I.30T composite produced by melt extrusion and injection molding, and explained the different behavior of basal reflection measured in reflection and transmission modes of XRD pattern by the anisotropic effect of the injection molding forcing the nanoclay platelets to be oriented preferentially parallel to the plane of the samples.…”
Section: Fig 3 Nanoclay Single Particles and Unexfoliated Agglomerates In The Film Skin Layermentioning
confidence: 78%
See 1 more Smart Citation
“…The disappearance of this peak by transmission XRD and appearance by reflection XRD analysis confirms the assumption about the preferential orientation of clay crystallites in the PAnanoclay composite. Abdelwaha et al [16] observed a similar preferred orientation effect for polyamide-Nanomer I.30T composite produced by melt extrusion and injection molding, and explained the different behavior of basal reflection measured in reflection and transmission modes of XRD pattern by the anisotropic effect of the injection molding forcing the nanoclay platelets to be oriented preferentially parallel to the plane of the samples.…”
Section: Fig 3 Nanoclay Single Particles and Unexfoliated Agglomerates In The Film Skin Layermentioning
confidence: 78%
“…Approximately a triple increase of the broadening of this reflection from 1.1° to 3.1°, that corresponds to decrease of the effective X-ray crystallite size from 6.4 nm to 2.6 nm, or decrease of the average number of clay layers in [001] direction of the crystallites from 3 to 1.7, was observed for the nanoclay in the composite. This result can be explained by the appearance of partially exfoliated crystallites of nanoclay in the composite, but might also indicate an unevenly delaminated or polymer intercalation and gradients in d-spacings of the clay crystallites [16]. The low intensity of this reflection, related to the low concentration of partially exfoliated clay crystallites in the composite, allowed us to infer that the concentration of intercalated nanoclay crystallites is small and most of the silicate layers of crystallites in the nanocomposite were exfoliated or delaminated.…”
Section: Fig 3 Nanoclay Single Particles and Unexfoliated Agglomerates In The Film Skin Layermentioning
confidence: 98%
“…However, polymer nanocomposites are usually in intercalated and/or exfoliated form. 4548 These morphologies are advantageous for improved mechanical properties and barrier properties. Polymer/nanoclay nanocomposite has gained interest in food packaging applications.…”
Section: Polymeric Nanocomposites In Packagingmentioning
confidence: 99%
“…Equibiaxial extensional flows are especially efficient for this purpose because the associated material viscosity is six times greater than the shear case . Improved dispersion of nanocomposite fillers using continuous polymer processing techniques especially melt extrusion has possessed a great interest in recent years . This cost‐effective technology assisted with atmospheric gases is able to produce nanocomposites with enhanced properties for many applications such as electromagnetic interference shielding, sensor applications, and high‐performance polymers …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33] Improved dispersion of nanocomposite fillers using continuous polymer processing techniques especially melt extrusion has possessed a great interest in recent years. [33][34][35] This cost-effective technology assisted with atmospheric gases is able to produce nanocomposites with enhanced properties for many applications such as electromagnetic interference shielding, sensor applications, and highperformance polymers. [36][37][38] In this work, EVOH was compounded with NC at a loading of 5% by weight using traditional TSE or SGAP with N 2 or CO 2 as the blowing agent.…”
mentioning
confidence: 99%